Beyond the Islamic State and Secularism: Nahdlatul Ulama and the Search for Religious–Nationalist State Model - M. Zaki Mubarak; Idris Thaha (Refleksi: Jurnal Kajian Agama dan Filsafat, 2026)
This article aims to analyze the dynamics of politico-religious thought within Nahdlatul Ulama (NU) concerning the relationship between Islam and the state in Indonesia, with particular reference to the ideas of Wahid Hasyim, Abdurrahman Wahid, and Salahuddin Wahid. Existing studies primarily focus on institutional or ideological debates on Islam and the state, while little attention has been given to the internal intellectual evolution of religion–state thought within Nahdlatul Ulama across generations. Employing a qualitative approach, this study uses an intellectual comparative method by examining key writings, speeches, and the historical contexts shaping the thought of these three figures. The article explores patterns of continuity and changes in NU’s responses to the question of the state foundation within a pluralistic society. The findings reveal that NU’s political thought has evolved historically and is not monolithic; rather, it reflects three major tendencies: shari‘a formalism, religious substantivism supporting pluralist secularism, and religio-nationalism as a synthesis. Wahid Hasyim represents a formalistic orientation that emphasizes the institutionalization of Islamic principles within the state; Abdurrahman Wahid advances a substantive approach that rejects formalization and support pluralist secular state; while Salahuddin Wahid proposes a religio-nationalist formulation that accommodates religious values without establishing them as the formal basis of the state. The study finds that these shifts are shaped by historical and sociological dynamics, including constitutional processes and the flexibility of Sunni fiqh traditions. It concludes that the relationship between religion and the state within NU constitutes a dynamic spectrum, with religio-nationalism emerging as the most adaptive model for reconciling religiosity and pluralism in Indonesia’s democratic context.